Sea fortune literature and navigation - Wolf, Burkhardt 1969- (De Gruyter, 2020)
Sea fortune has always been an issue of good faith and good navigation. While in antiquity, fortuna gubernatrix was praised for shielding the seaborne trade, in the Renaissance fortuna symbolized the conquest of chance and danger. Under such auspices, while relying on risk technologies modern seafaring has never lost its adventurous dimension. Understanding their origin remains a challenge for the history of science and the history of literature
Keywords: Geschichte; Cultural History; Literary Studies; Media History; Seafaring; LITERARY CRITICISM / General; Seehandel; Glück -- Motiv; Literatur; Seeschifffahrt -- Motiv; Seeschifffahrt; Schiffsreise; Schiffsreise -- Motiv; Risiko -- Motiv